Refining the stars: reducing the Keck Observatory calibration error with a cutting-edge calibration screen - Solheim, Kennedy, author; Fankell, Doug, advisor; Stansloski, Mitchell, committee member (Colorado State University. Libraries, 2025)
The Keck Observatory's telescopes are among the most advanced and productive in the world, enabling groundbreaking astronomical research [4]. However, the current calibration system - consisting of shining projectors onto the uneven dome surface - introduces an error of approximately 30%, impacting observational data and discoveries. This honors thesis details the development of a 1/10th scale prototype - where the full scale would be 12-meters in diameter to fit the 10-meter telescope - for an improved calibration system, designed by an interdisciplinary team including three mechanical engineering students and two electrical engineering students. The goal is to reduce said errors to an initial target of 6% or less. The design process lasts a full academic year, relying on a strong relationship between mechanical and electrical subsystems to achieve precise alignment and innovation. While the mechanical engineering team develops structural aspects, motion mechanisms, mounting mechanisms, and stability, the electrical engineering team establishes control systems, safety mechanisms, lighting aspects, and power distribution systems. The prototype leverages non-conventional solutions developed by a team of engineering students dedicated to learning and simulating real-world operational conditions. This senior design project is a significant step in the Keck Observatory's observational capabilities, allowing this year's team to generate ideas and determine feasibility to pass on to next year's team for further development. By addressing these current limitations of the telescopes, the team's efforts in this project will help the W.M. Keck Observatory remain the leading ground telescope in scientific discovery with more accurate astronomical data in addition to contributing to the improvement of calibration systems as a whole. The outcomes of this project include team collaboration, design methodology, testing, prototyping, and understanding the improvements that can be made with cost and time constraints, providing a foundation for future development of the full-scale system in the years to come.
University Honors Program
Department of Mechanical Engineering
Senior Design Project
Keywords: calibration; Keck Observatory; senior design; engineering; telescope